CORPORATE SOCIAL RESPONSIBILITY COST AND SUSTAINABLE GROWTH OF LISTED MANUFACTURING FIRMS IN NIGERIA - Okezie, Stella Ogechukwu (Annals of Spiru Haret University. Economic Series, 2022)
The study examined the effect of corporate social responsibility cost on sustainable growth of listed firms in Nigeria. The study adopts ex-post facto research design. Fourteen (14) out of the 56 listed manufacturing companies on the Nigerian stock exchange as at 2021 were selected for the study. Data was analyzed using panel regression and Autoregressive Distribution Lag (ARDL) model. Findings from the study reveal that, corporate social responsibility cost denoted as social responsibility cost and environmental cost has a long run relationship with sustainable growth of listed manufacturing firms in Nigeria as measured by the bounds test using the Wald statistics. Furthermore, the results also reveal short run relationship with a speed of adjustment to long run equilibrium at 77.95% significant at 5% level of significance. It is thus recommended that manufacturing firms should continue to invest in corporate social responsibility as this has a significant effect on their sustainability. Firms must sustain the current corporate social responsibility strategy and improve on ways to be cost efficient while still maintaining an effective corporate social responsibility strategy that will put the firms in good light with consideration to environmental responsiveness.